Fermi Unassociated Sources in the MeerKAT Absorption Line Survey - Morgan Himes; Preshanth Jagannathan; Dale A. Frail; Frank Schinzel; Neeraj Gupta; S. A. Balashev; F. Combes; P. P. Deka; H.-R. Klöckner; E. Momjian; J. D. Wagenveld (The Astrophysical Journal)
Over 2000 γ -ray sources identified by the Large Area Telescope on NASA's Fermi Gamma-ray Space Telescope are considered unassociated, meaning that they have no known counterparts in any other frequency regime. We have carried out an image-based search for steep spectrum radio sources, with in-band spectral index < −1.4, within the error regions of Fermi unassociated sources using 1–1.4 GHz radio data from the MeerKAT Absorption Line Survey (MALS) data release. The first MALS data release with a median rms noise of 22–25 μ Jy and 735,649 sources is a significant advance over past image-based searches with improvements in sensitivity, resolution, and bandwidth. Steep spectrum candidates were identified using a combination of in-band spectral indices from MALS and existing radio surveys. We developed an optical and infrared source classification scheme in order to distinguish between Galactic pulsars and radio galaxies. In total, we identify nine pulsar candidates toward six Fermi sources that are worthy of follow-up for pulsation searches. We also report 41 steep spectrum radio galaxy candidates that may be of interest in searches for high-redshift radio galaxies. We show that MALS, due to its excellent continuum sensitivity, can detect 80% of the known pulsar population. This exhibits the promise of identifying exotic pulsar candidates with future image-based surveys with the Square Kilometre Array and its precursors.